Gerenciamento de nível em reservatório de líquidos por lógica Fuzzy e controle PID - Oliveira Junior, Cidinei Manoel de (2023)
This work presents a system widely used in industrial installations: the tank level control system. The designed system performs a level control, through the CodeSys software and also Matlab/Simulink, of a tank which is simulated from the Factory I/O software. To control the system, two controllers were developed: a Fuzzy and a PID, using the trial and error method to find the parameters of the PID controller and to elaborate the Fuzzy control, the Matlab Fuzzy Logic Designer tool was used together with the Simulink for your review. This project describes the functioning of the simulated tank system, the elaboration of the programming used in the PLC and the simulation devices, the OPC communication protocol for communication from the PLC to Matlab and Factory I/O, the way to obtain the controller parameters PID, the construction of the Fuzzy controller, the response graphs to the controls and the analysis of the response of each controller, these that demonstrated a satisfactory control of the simulated tank system.